Sekolah Ramah Anak Dalam Mencegah Perilaku Bullying di Sekolah Dasar - Nur Khoiriyah, Annisa; F. Ramadhan, Dadan; Sofyan, Muhammad (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
Bullying remains a serious issue in elementary schools and has negative impacts on children's psychological and social development. To address this problem, the Child-Friendly School (SRA) Program is implemented to create a safe, comfortable, inclusive, and violence-free learning environment, while also ensuring the protection of children's rights. This study aims to analyze the implementation of the SRA program in preventing bullying behavior at Labschool Elementary School UPI Cibiru. This research employs a qualitative descriptive approach. Data collection techniques include in-depth interviews, direct observation, and document analysis. The research informants consist of the principal, teachers, students, and parents. The analysis focuses on three main aspects: (1) anti-bullying policy planning, (2) implementation of the SRA program, and (3) evaluation of the program’s impact on the school environment. The findings indicate that although cases of bullying still occur, the school has systematically implemented anti-bullying policies, provided teacher training, and actively involved parents and students. An empathetic approach grounded in Islamic values also supports the creation of a friendlier and safer school environment. Furthermore, the SRA program has proven effective in increasing awareness among all school members about the importance of bullying prevention. It can be concluded that the implementation of the Child-Friendly School program significantly contributes to bullying prevention efforts in elementary schools and promotes the creation of an inclusive learning environment centered on children's well-being